Development and Evaluation of Non-Formal Education Programme "Programming" in the Environment of Distance Education Secondary Schooludy - Katans, Edgars; Jurgena, Inese; Katane, Irēna; Svareniece, Benita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
One of the main aims for the modern education is to facilitate the sustainability of information society, therefore an important feature that highlights differences in the education of the 20th and 21st century is the variety of information and communication technologies (ICT) and the expansion of their application in the education. The development of information and communication technologies caused far-reaching consequences in human life and activities and also seriously influenced education, providing wide perspective for the development of distance education environment. This article represent the results of theoretical and empirical research in the sphere of IT education and computer science. The aim of the research: to substantiate theoretically, develop and evaluate the non-formal education programme “Programming” in the environment of distance education secondary school on the basis of personal experience regarding distance education and pedagogy, the programmer’s professional competence and research results.